Beyond silence and fluency: Rethinking Chinese international students’ class participation and engagement in Canadian higher education - Chi, Chenkai; Xiang, Beibei (Journal of International Students, 2026)
This qualitative study explores how Chinese international graduate students perceive and negotiate classroom participation and engagement at a Canadian university. Drawing on the notions of investment and time inheritance, this study examines how identity, linguistic and cultural capital, ideological expectations, and temporal resources interact to shape Chinese international students’ academic behavior. Sixteen graduate students from diverse faculties at a Canadian university were interviewed. Thematic analysis revealed that classroom participation and engagement are determined not only by language fluency or pedagogical familiarity but also by inherited time, neoliberal performance pressures, and classroom power dynamics. While some Chinese international students found affirming spaces for cultural identity and relational trust, others encountered marginalization through monolingual norms and deficit discourses. The study advances a multidimensional understanding of class participation and engagement for Chinese international graduate students, calling for inclusive pedagogical practices that honor linguistic diversity and temporal equity.